Mapping weather, water, ice and climate (WWIC) information providers in polar Regions: who are they and who do they serve? - Haavisto, Riina; Lamers, Machiel; Thoman, Rick; Liggett, Daniela; Carrasco Cerda, Jorge Fernando; Dawson, Jackie; Ljubicic, Gita; Stewart, Emma (My University, 2020)
Environmental conditions in Polar Regions are becoming more dynamic due to climate change. As sea ice melts, the range of human activities in Polar Regions are projected to increase, while weather conditions are becoming more extreme and unpredictable. Provision and use of weather, water, ice and climate (WWIC) information plays a key role in ensuring that polar activities are conducted as safely as possible and can contribute to a reduction of the environmental footprint of human activities. In this article, we explore the WWIC information provider landscape in a polar context, drawing on a database we compiled to characterize the diversity of providers. The database is built on available literature and on an extensive desk-based research of WWIC information provider websites. We analyse the 374 providers categorized by (a) institutional background (public vs private), (b) the position of the provider relative to activities in the WWIC information space, and (c) the users they serve. While governmental institutions have a strong presence in information provision, new types of providers are now entering the scene. Scientific actors seem to play a substantial role as users as well as major providers of WWIC information services.
Keywords: weather; water; ice and climate (wwic) information; polar regions; information providers; climate services